2015
DOI: 10.5330/1096-2409-19.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Comprehensive School Counseling Programs and Positive Behavioral Interventions and Supports to Maximize School Counselors’ Efforts

Abstract: oo many schools are still struggling to create the nurturing, positive, and safe environments that we know are needed to boost student achievement and success. No student or adult should feel unsafe or unable to focus in school, yet this is too often a reality" (U.S. Department of Education, 2014, p. i). The U.S. Department of Education (2014) recommends that schools implement evidence-based strategies to promote safe schools, including the use of tiered supports differentiating students' needs and interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…These two frameworks were described as functioning "hand-in-hand" and "overlap[ping]," particularly in relation to data and language. Although scholars have conceptually proposed the alignment or integration between comprehensive school counseling programs and PBIS (ASCA, 2014;Goodman-Scott et al, 2016), the present study appears to be the first to empirically describe this integration, and does so using rigorous trustworthiness strategies across multiple participants.…”
Section: Ramp and Pbismentioning
confidence: 97%
See 2 more Smart Citations
“…These two frameworks were described as functioning "hand-in-hand" and "overlap[ping]," particularly in relation to data and language. Although scholars have conceptually proposed the alignment or integration between comprehensive school counseling programs and PBIS (ASCA, 2014;Goodman-Scott et al, 2016), the present study appears to be the first to empirically describe this integration, and does so using rigorous trustworthiness strategies across multiple participants.…”
Section: Ramp and Pbismentioning
confidence: 97%
“…On the other hand, studies on RAMP school counselors found they appreciated using data (Ward, 2009;Young & Kaffenberger, 2011). Further, data is a key component of PBIS (OSEP Center on PBIS, 2015), and scholars discuss school counselors' involvement in data within PBIS implementation theoretically and through single-subject case study research (e.g., Goodman-Scott et al, 2016;Martens & Andreen, 2013). According to previous research and the current study, implementing data-driven frameworks such as RAMP and PBIS may increase school counselors' comfort with data.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the critical tasks for school counselors is developing productive strategies and interventions to maximize their efforts and time (Goodman-Scott, 2013). One such effort is ASCA's recommendation to utilize positive behavioral interventions and supports (PBIS) to strengthen implementation of a comprehensive school counseling program (Goodman-Scott, Betters-Bubon, & Donohue, 2015). PBIS and other systemic and evidence-based interventions prioritize creating a positive and healthy school climate by instruction and consistent, school-wide behavioral expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Applying a multitiered system of supports (MTSS) datadriven framework enhances school counselors' ability to implement a comprehensive school counseling program with targeted interventions promoting students' academic, career, and social/emotional growth (ASCA, 2018b;Goodman-Scott et al, 2015;Ziomek-Daigle et al, 2016). MTSS encompasses three tiers of prevention, with each tier addressing a specific level of student need (North Carolina Department of Public Instruction, 2020).…”
mentioning
confidence: 99%